Pengaruh Digitalisasi Pajak dan Peran Relawan Pajak Terhadap Kepatuhan Wajib Pajak Dalam Melaporkan SPT Tahunan di KPP Pratama Jakarta Gambir Tiga - Evan Fulvian; Notika Rahmi (Jurnal Ilmu Administrasi Publik, 2025)
This study aims to analyze the influence of tax digitalization and the role of tax volunteers on individual taxpayer compliance in submitting annual tax returns at KPP Pratama Jakarta Gambir Tiga. Employing a quantitative, associative research method, data were collected via questionnaires from 100 individual taxpayers and analyzed using multiple linear regression with SPSS. Tax digitalization includes the use of e-filing, e-form, and DJP Online, while the volunteer role encompasses education, assistance, and outreach. The results reveal that tax digitalization not significantly and the role of tax volunteers significantly and positively affect taxpayer compliance, with contributions of 0.21% and 20.34% respectively. Simultaneously, both variables account for 20.6% of the variation in compliance behavior. The findings highlight the practical value of integrating digital services and educational outreach in enhancing voluntary tax compliance within a self-assessment tax system. Keywords tax digitalization; tax volunteers; tax compliance; annual tax return; DJP Online